The Reported Adverse Effects Related to Biological Agents Used for the Treatment of Rheumatic Diseases in Turkey - Erkan KILIÇ,; Gamze KILIÇ,; Özgür AKGÜL,; Gürkan AKGÖL,; Salih ÖZGÖÇMEN1, (Archives of Rheumatology, 2013)
Objectives: This study aims to review the reported adverse events related to the use of biological agents used for the treatment of rheumatic diseases in Turkey. Patients and methods: Between January 2000 and January 2012, the literature was searched in English and Turkish for case reports and case series using the MedLine, Web of Science, and Scopus databases reporting adverse effects related to the use of biological agents including infliximab, etanercept, adalimumab, anakinra, rituximab which were used for the treatment of rheumatic diseases. Results: A total of 53 patients (21 males, 32 females) with rheumatic disease who suffered from adverse effects related to the use of biological agents were reported in Turkey in the literature. The mean age was 39.0±15.6 years, while the mean disease duration was 10.6±8.2 years. The mean time from the initiation of the biological agents to the onset of the adverse events was 8.8±9.2 months. The most frequently seen biological agentrelated adverse effects were observed in patients with ankylosing spondylitis (AS) and rheumatoid arthritis (RA). Tuberculosis (TB) was the most commonly reported adverse effect with in 14 patients (26.4%). Other adverse events included psoriasis (15.1%), solid tumors (7.6%), lymphoma (5.7%), drug-induced lupus (3.8%), and menstrual bleeding (3.8%). A total of 77.4% patients who suffered from adverse events discontinued biological therapies. Conclusion: Biologic agents are relatively safe; however, they may rarely lead to serious adverse events. As tuberculosis is a moderate endemic disease in Turkey, patients who are scheduled for biological agents (anti-TNF and abatacept particularly) should be informed about the potential risks of biological therapy and monitored closely before and after the initiation of treatment.